Stability, transport and ecosystem effects of graphene in water and soil environments. Issue 17 (13th April 2017) - He, Kai; Chen, Guiqiu; Zeng, Guangming; Peng, Min; Huang, Zhenzhen; Shi, Jiangbo; Huang, Tiantian
Abstract : Graphene nanomaterials (GMs), such as graphene oxide (GO) and reduced graphene oxide (rGO), have been widely applied in various fields. Abstract : Graphene nanomaterials (GMs), such as graphene oxide (GO) and reduced graphene oxide (rGO), have been widely applied in various fields. Due to the rapid increase in production and application, the inevitable release of GMs into water and soil environments poses potential health and ecosystem risks. Upon exposure, the behavior, transport, and fate of GMs may be altered after interacting with the relevant environmental conditions. GMs can affect the microbial communities as well. Thus, it is imperative to understand the interaction between the GMs and the environmental systems for predicting their risks. For this purpose, this review highlights the influence of the most relevant environmental factors on the stability, aggregation, and transformation of GMs in aquatic environments. Moreover, the transport of GMs and microbial communities changes have also been presented based on the recent findings. To the best of our knowledge, this review covered most of the recent related studies and will allow for accurate predictions of the fate and risks associated with GMs. In consideration of the diversity of GMs and the complexity of environmental factors, further studies should be focused on their inherent properties and amicable development.